A Research Evaluating the Attitudes of Local People Towards the Effects of Tourism in Bozcaada - Esin Bildin; Ahmet Vatan (Journal of Economy Culture and Society)
This study was conducted in order to reveal local people’s commitment to Bozcaada and their attitudes towards both the effects of tourism and the development of tourism in Bozcaada. Place Attachment, Tourism Development and the Effects of Tourism were scales used in this study, by applying the questionnaire method. The hypotheses indicated that the relationship between tourism development, interaction with tourists, tourism dependence on income source and self-identification with Bozcaada was examined by applying Chi-Square test to certain demographic variables. There was no significant relationship found between being native islander and lifetime in Bozcaada and having a source of income due to tourism. There was a significant relationship between the frequency of interaction with tourists and lifetime in Bozcaada along with the local people existing in the tourism sector as a workforce. There was no significant relationship between having tourism as a source of income and support of tourism development. There was a significant relationship between the education level of local people and the support of tourism development and also between lifetime in Bozcaada and identifying oneself with Bozcaada. The economic and socio-cultural effects of tourism were perceived as positive and the environmental impacts of tourism were perceived as negative in Bozcaada at high level.